Improving Grade V Students’ Mathematics Learning Outcomes on FPB Topics Through Problem-Based Learning - Siti Aisyah Apriliani; Sri Muryaningsih (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The low mathematics learning outcomes in the Biggest Common Factor (FPB) material in grade V of SD Negeri 3 Larangan is due to learning that is still teacher-centered so that students are less active in understanding concepts and solving problems. This research aims to improve student learning outcomes in the cognitive, affective, and psychomotor domains through the application of the Problem Based Learning (PBL) model. The method used is the Kemmis and McTaggart model Class Action Research (PTK) which is carried out in two cycles. The research subjects amounted to 23 students in grade V of SD Negeri 3 Larangan. Data collection techniques are carried out through tests, observations, interviews, and documentation, while data analysis uses quantitative and qualitative approaches. The results of the study show that the application of the PBL model is able to improve student learning outcomes. Cognitive learning completeness increased from 30.43% in the pre-cycle to 63% in the first cycle and 78% in the second cycle. In addition, the affective and psychomotor aspects of students have also improved which is shown through increased discipline, cooperation, responsibility, confidence, and students’ skills in solving and presenting problem-solving results. Thus, the Problem Based Learning model is effectively used to improve mathematics learning outcomes in FPB materials in elementary schools.